Ergonomics of PET bottles - Dömötör, Csaba (Design of Machines and Structures, 2025)
The article analyses the basic functions of standard-sized PET bottles from an ergonomic perspective. Accordingly, it analyses the storage, closing, opening, sealing, emptying, stability, gripping and information transfer functions from the user's perspective. It shows good and bad practices.